Behavior of CFRP partially wrapped square seawater sea-sand concrete columns under axial compression. (1st November 2020) - Yang, Junlong; Lu, Shiwei; Wang, Jizhong; Wang, Ziru
Highlights: Axial compressive behavior of partially CFRP wrapped square NC and SSC columns was investigated. Parameters affecting the mechanical performance of tested specimens were discussed. A new stress-strain model was developed for partially FRP confined square concrete. The performance of existing models in predicting the ultimate conditions was examined. Abstract: The innovative use of seawater sea-sand concrete (SSC) with fiber-reinforced polymer (FRP) has the potential to offer significant advantages in marine constructions, which leads to extensive projects conducted to investigate the mechanical performance of FRP-SSC composite structures. This paper therefore presents an experimental study of CFRP partially wrapped square seawater sea-sand concrete columns under axial compression. Six CFRP strengthening schemes were designed for the external confinement and the effects of concrete type, clear spacing ratio, CFRP thickness and strengthening strategy on the stress-strain relationship were also investigated in this study. The test results show that similar axial compressive behavior was observed for CFRP partially wrapped normal concrete and seawater sea-sand concrete columns. Moreover, for the SSC specimens partially wrapped with two-layer CFRP strips, the average ultimate strengths were increased by 13.6–36.6% with the decrease of clear spacing ratio, while the average ultimate strains were improved by 22.3–91.9%. Furthermore, the maximum enhancement of 57.6% and 108.8% can be achieved for the ultimate strength and strain respectively when the thickness of CFRP sheets was double increased. In addition, a comprehensive analysis of existing stress-strain models for FRP confined concrete in square columns was conducted and a test database was also assembled to examine the performance of several selected models in predicting the ultimate conditions. Finally, a new stress-strain model was proposed for FRP partially wrapped square concrete in this study and the proposed model was proven to be superior to all the other selected models by comparing the experimental observations with theoretical predictions.